Assessment of Mothers’ Knowledge about Their Children with Sickle Cell Anemia and Non-Pharmacological Approaches to Pain Management in Basra Center for Hereditary Blood Diseases - Abd-Alrazzaq, Aula; Aziz, Afifa (Iraqi National Journal of Nursing Specialties, 2021)
Objective(s): To assess mothers’ knowledge about their children with sickle cell anemia and non-Pharmacological approaches to pain management and found some relationship between mothers knowledge and their demographic data of age, level of education, and occupation. Methodology: A descriptive design used in the present study established was for a period from September 19th, 2020 to March 30th, 2021. The study was conducted on a non-probability (purposive) sample of (30) mother their children with sickle cell anemia was chosen. The data were analyzed through the application of descriptive and inferential statistical approaches which are applied by using SPSS version 22.0. Results: The findings of the study indicated that moderate levels of knowledge toward their children with sickle cell anemia about non-pharmacological approaches to pain management. No significant relationship among mothers’ knowledge with all demographic at p-value= 0.05 except, there are relationship between mothers’ knowledge and Education, as well as there are relationship between mothers’ knowledge and Occupation at p-value= 0.05. Recommendations: The researcher recommends that need to educational program about non pharmacological to pain management to improve and enhance level of mother’s knowledge. There is a real need for coordination with the media in order to increase mothers’ knowledge about non-pharmacological to pain management.